Nanocrystalline coatings properties forecasting - Eremin, E. N.; Yurov, V. M.; Guchenko, S. A.; Laurynas, V. Ch. (IOP PUBLISHING LTD, 2017)
The paper considers various properties of nanocrystalline coatings. The methods of determining the surface tension of the deposited coating on the basis of the size dependence of their physical properties. It is shown that predict the mechanical properties of the coatings, their melting point, heat resistance, wear resistance, corrosion resistance, etc. It can be based on a theoretical evaluation of the surface tension.